Apteronotus caudimaculosus n. sp. (Gymnotiformes: Apteronotidae), a sexually dimorphic black ghost knifefish from the Pantanal, Western Brazil, with a note on the monophyly of the A. albifrons species complex - de Santana, Carlos David (Zootaxa, 2003)
Apteronotus caudimaculosus, a new species of ghost knifefish with males having greatly elongated snouts, is described from the Pantanal wetlands, Paraguay River basin in Western Brazil. It is distinguished from its congeners by two light bands encircling the caudal peduncle, the first caudal band with irregular spots throughout its development. The presence of two light bands can be used to identify a monophyletic clade in Gymnotiformes, the so-called A. albifrons species complex. This group comprises A. albifrons, A. caudimaculosus and at least six undescribed species. An artificial key to identification of species currently in Apteronotus (sensu stricto) is provided.